Health education as a tool in the prevention of childhood pneumonia: a case report (Research, Society and Development, 2021)
Pneumonia is one of the most relevant causes of mortality in the world and one of the most prevalent diseases in childhood, and can cause severe hospitalizations in children under five years of age. Therefore, it is important to emphasize the importance of vaccination in preventing pneumonia, as well as encouraging factors that protect the child's health. The study aimed to report an experience of academics in the health area, which occurred through the implementation of a health education action on preventive measures against childhood pneumonia, aiming at promoting vaccination, as well as the preventive habits of the disease. This is a descriptive study, of the experience report type, based on the problematization methodology of the Arco de Maguerez. Among the main results obtained, it was found that the action contributed to the recognition of the main risk factors and the importance of the vaccination status. of the child, thus being able to minimize future pneumonia cases, as well as the occurrence of its injuries. According to the data observed in this study, it is possible to conclude that health education represents an important tool in mitigating the risk factors that involve childhood pneumonia. Finally, it is hoped that this production will foster future research aimed at developing strategies to stimulate care for children and adolescents, as well as the mitigation of the studied pathology.